Estrutura populacional do Prochilodus brevis (SteindaChner,1875) (Characiformes, Prochilodontidae) em sistema de reservatórios de uma bacia hidrográfica do semiárido neotropical, Brasil - Moreira, Suzany Iasnaya Lopes (Universidade Federal Rural do Semi-Árido, 2015)
Prochilodus brevis (curimatã) is a migratory and endemic fish species of the hydrographic basin in semiarid region, occurring in rivers and reservoirs. The aims of this study was evaluate the population structure species in two reservoirs (Pau dos Ferros and Santa Cruz Reservoirs) that are located in the hydrographic basin of the Apodi/Mossoró River. The biological material was obtained through quarterly collections carried out from February/2011 to November/2012, using gillnets from 12 to 70mm. We evaluated Catch Per Unit Effort by the number (CPUEn), the length structure in 3 cm classes, sex ratio, the length-weight relationship (Wt), condition factor (K), the length at first maturity and the gonadosomatic index (GSI). The Pau dos Ferros Reservoir showed a higher abundance and better structured population with capture young individuals and adults in higher abundance. In the Pau dos Ferros Reservoir the distribution of the species was homogeneous, while in the Santa Cruz reservoir the species had a higher capture at at fluvial region. The sex ratio remained within the expected of 1:1 both the Pau dos Ferros reservoir as to the Santa Cruz reservoir. Isometric growth of the species (b=3.0109) was in Pau dos Ferros reservoir and allometric negative (b=2.6710) in the Santa Cruz Reservoir. Furthermore, the condition factor indicated that the population of the species in Pau dos Ferros reservoir had a better physiological condition. The length at first maturity for the Pau dos Ferros reservoir and Santa Cruz were 16.97cm and 17.40cm, respectively. Reproductive investment was similar between the reservoirs; however, for the population of the Santa Cruz reservoir is not being reflected in the recruitment of new individuals to the population, since that capture of juveniles was low. The results found suggested that the species maintain viable populations in Pau dos Ferros Reservoir, on the other hand in the Santa Cruz reservoir, probably in this reservoir species not found appropriate places to spawn and/or development of juveniles. Thus, the results suggested that the construction of the Santa Cruz reservoir was detrimental to the population of P. brevis and if appropriate measures are not taken handling species may disappear from the reservoir
Fish; Curimatã; Species migratory; Spawning; Ecology
Keywords: Population structure of Prochilodus brevis (Steindachner, 1875) (Characiformes, Prochilodontidae) in reservoir system in a basin of neotropical semiarid, Brazil; Peixe; Curimatã; Espécie migrador; Desova; Ecologia; CIENCIAS BIOLOGICAS::ECOLOGIA